Pattern of ivermectin (sheep) and doramectin (cattle) residues in muscular tissue from various anatomical locations - Moreno Torrejon, Laura (2008)
This trial reports comparative drug residual concentrations in muscular tissue obtained from various anatomical locations after subcutaneous administration of ivermectin (IVM) to sheep and topical treatment with doramectin (DRM) to calves at recommended therapeutic dose rates. Seven muscle samples from different anatomical locations (rhomboideus, supraspinatus, semitendinosus, gluteus medius, longissimus dorsi thoracis, intercostales and diaphragma) were collected at several post-treatment sampling times. Samples were frozen at-20 degrees C until analyzed by HPLC. The highest IVM residual concentrations in muscular tissue from the different locations were found at 15 days post-treatment in sheep. Although the highest IVM mean concentrations were measured at 15 (16.8 +/- 5.17 ng g(-1)) and 20 (10.5 +/- 4.06 ng g(-1)) days post-administration in the intercostales muscles, at 30 days post-administration, the IVM concentration in this location was similar to that measured in the rhomboideus and diaphragma muscles. DRM residual concentrations were quantified in muscular tissue from all anatomical locations after topical administration to calves. Maximum residue level was observed at 10 days post-treatment in all anatomical sites. The diaphragma muscle showed the highest DRM residue levels at 2 (22.0 +/- 4.35 ng g(-1)), 5 (45.2 +/- 3.78 ng g(-1)) and 10 (57.9 +/- 9.57 ng g(-1)) days post-treatment in calves. These results demonstrated that the pattern of residue depletion from muscular tissue may differ according to its anatomical locations and/or physiological role. This should be considered in implementing residue control strategies in meat safety assurance for human consumption.